Induction of diabetes by Tacrolimus in a phenotypic model of obesity and metabolic syndrome - Teixidó-Trujillo, Silvia; Porrini, Esteban; Menéndez-Quintanal, Luis Manuel; Torres-Ramírez, Armando; Fumero, Cecilia; Rodríguez-Rodríguez, Ana Elena (Frontiers in Endocrinology, 2024)
Introduction The pathogenesis of Post-Transplant Diabetes Mellitus (PTDM) is complex and multifactorial and it resembles that of Type-2 Diabetes Mellitus (T2DM). One risk factor specific to PTDM differentiates both entities: the use of immunosuppressive therapy. Specifically, Tacrolimus interacts with obesity and insulin resistance (IR) in accelerating the onset of PTDM. In a genotypic model of IR, the obese Zucker rats, Tacrolimus is highly diabetogenic by promoting the same changes in beta-cell already modified by IR. Nevertheless, genotypic animal models have their limitations and may not resemble the real pathophysiology of diabetes. In this study, we have evaluated the interaction between beta-cell damage and Tacrolimus in a non-genotypic animal model of obesity and metabolic syndrome. Methods Sprague Dawley rats were fed a high-fat enriched diet during 45 days to induce obesity and metabolic dysregulation. On top of this established obesity, the administration of Tacrolimus (1mg/kg/day) during 15 days induced severe hyperglycaemia and changes in morphological and structural characteristics of the pancreas. Results Obese animals administered with Tacrolimus showed increased size of islets of Langerhans and reduced beta-cell proliferation without changes in apoptosis. There were also changes in beta-cell nuclear factors such as a decrease in nuclear expression of MafA and a nuclear overexpression of FoxO1A, PDX-1 and NeuroD1. These animals also showed increased levels of pancreatic insulin and glucagon. Discussion This model could be evidence of the relationship between the T2DM and PTDM physiopathology and, eventually, the model may be instrumental to study the pathogenesis of T2DM.